Dental cavities, periodontal disease, and oral hygiene knowledge of post-discharge explicit health guarantees pregnant patients in a family health center in Chillán - Salazar, María Jesús; Parra, Julio (Revista Chilena de Salud Pública, 2018)
The most prevalent oral diseases in Chile are dental cavities and periodontal disease, and pregnant women are not the exception. This study investigates this population. Objective: To evaluate the effect of dental interventions on the number of dental cavities and the periodontal health status of post-discharge participants of the 2013 GES Dental Program for Pregnant Women in the Violeta Parra CESFAM (primary care center) in Chillán, Chile. Materials and methods: An analytical cross-sectional study was conducted with 67 pregnant women discharged in 2013 and evaluated in a dental check-up in 2016. Sources of information were: clinical examination, dental anamnesis, clinical records, and a survey of oral hygiene habits. The study was authorized by the Ethics Committee of the Chillán Herminda Martin Hospital. Descriptive and inferential statistics were used with the SPSS program, with α = 0.05. Results: Dental cavities significantly decreased from 10.34 to 0.81 post intervention (p < 0.0001). While 97% of participants exhibited bad or fair periodontal health in 2013, this variable noticeably improved in 2016, with only 4.5% of users in this category (p < 0.0001). Regarding oral hygiene habits, participants used a correct brushing technique, and they considered toothbrushing to be the most important tool to prevent cavities. Conclusion: The dental intervention performed by the GES Program for Pregnant Women significantly decreased the number of post-discharge dental cavities. Periodontal health of the participants improved and was maintained three years after discharge from the program.